Dispersive Liquid-Liquid Microextraction Based Preconcentration of Selected Pesticides and Escitalopram Oxalate, Haloperidol, and Olanzapine from Wastewater Samples Prior to Determination by GC-MS - Bozyigit, Gamze Dalgic; Ayyildiz, Merve Firat; Chormey, Dotse Selali; Engin, Guleda Onkal; Bakirdere, Sezgin (OXFORD UNIV PRESS INC, 2021)
Background: Determination of emerging pollutants including pharmaceuticals, pesticides, industrial chemicals and hormones in different environmental samples is very important for human health. Objective: Experimental design enabled parameters to be evaluated for their effects onextraction output as well as their interactive effects. Method: A multivariate experimental design was used to attain optimum conditions of a dispersive liquid-liquid microextraction method for preconcentration of pesticides and pharmaceuticals for determination by GC-MS. Results: The optimum parameters suggested by the design model were 200 mu L of chloroform, 1.96 mL of ethanol, and 40 s vortexing period. LOD and LOQ were calculated using linear calibration plots of the analytes developed in the standard concentration range of 2.0 mu g/L-2.0 mg/L. Conclusions: Enhancement in detection power of the analytes recorded by the optimized method with respect to direct GC-MS determination (based on LOD values) was in the range of 3.6 and 539 folds. Spiked recovery experiments for municipal, medical, and synthetic wastewater samples yielded low recovery results when calculated against aqueous standard solutions. Matrix matched calibration standards were used to mitigate interferences from the waste samples and the percent recoveries obtained were close to 100%. This established accuracy and applicability of the developed method.
Keywords: REMOVAL; PHARMACEUTICALS; OPTIMIZATION; HERBICIDES; Chemistry; Food Science & Technology